The Eligibility Game: Legal Issues Relating to Participation in Intercollegiate Athletics - Milburn, Steven D. (My University, 1985)
This paper explored some of the issues and particular cases concerning athletic eligibility that have been brought before the courts. It looked at the decisions and reasoning of the courts in those cases and attempted to project the present status of eligibility cases and how those cases may be decided in the future. It focused on whether or not the NCAA is a state actor, and eligibility cases regarding the 1.6 rule, the 2.0 rule, and sitting out a year after transferring among others.
Keywords: legal issues; eligibility